1996
DOI: 10.1111/j.1574-6968.1996.tb08518.x
|View full text |Cite
|
Sign up to set email alerts
|

A common pathway of sulfide oxidation by sulfate-reducing bacteria

Abstract: The pathway of sulfide oxidation with oxygen as electron acceptor was studied with five strains of freshwater, marine and alkaliphilic sulfate‐reducing bacteria. Electrode measurements with washed cells indicated that all strains oxidized sulfide to elemental sulfur. In a second step, the elemental sulfur formed was disproportionated to sulfate and sulfide. During this phase, most of the disappeared sulfide was formed back. Since oxygen could be replaced by nitrate or nitrite as electron acceptor, the describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 16 publications
(19 reference statements)
6
32
1
Order By: Relevance
“…The mechanism by which oxygen-dependent growth occurs is not yet clear. Fuseler et al (7) recently reported that oxygen consumption in Desulfovibrio desulfuricans CSN was coupled to the oxidation of sulfide to sulfur, after which the sulfur underwent disproportionation to sulfide and sulfate. Oxygen was also reduced in a separate reaction, possibly involving a periplasmic cytochrome c capable of both reducing sulfur and being autoxidized by oxygen.…”
mentioning
confidence: 99%
“…The mechanism by which oxygen-dependent growth occurs is not yet clear. Fuseler et al (7) recently reported that oxygen consumption in Desulfovibrio desulfuricans CSN was coupled to the oxidation of sulfide to sulfur, after which the sulfur underwent disproportionation to sulfide and sulfate. Oxygen was also reduced in a separate reaction, possibly involving a periplasmic cytochrome c capable of both reducing sulfur and being autoxidized by oxygen.…”
mentioning
confidence: 99%
“…As such, SRB comprise a functional group within a sulfuretum, linking broad-scale cycling between sulfate and sulfide by ecological communities of SRB and sulfide-oxidizing bacteria (12,28). Biological reoxidation of reduced sulfur species typically occurs at oxic-anoxic transition zones and is attributed largely to phototrophs and chemolithotrophs.…”
mentioning
confidence: 99%
“…Thiosulfate is found naturally in anoxic environments (Höll 1979) and is widely used as an electron acceptor or as an electron donor (Jørgensen 1990;Jørgensen and Bak 1991). Despite this importance, no significant biological source of thiosulfate has been reported [see also Fuseler and Cypionka (1996)]. We thus believe that we have detected a potential biological source of thiosulfate, namely the widespread taurine (Huxtable 1992).…”
Section: Discussionmentioning
confidence: 85%